A PHILOSOPHICAL APPRAISAL OF CONSCIENCE AS A SUBJECTIVE NORM OF MORALITY - Nnachi, Charles Aruo; Nwinya, Stephen Chijioke; Ekpe, Patrick Prince; Ogwu, Denis Ejilekpang (EBSU Journal of Social Sciences and Humanities, 2024)
This work examines the concept of conscience as a subjective norm of morality. In his quest for happiness, modern man has reduced the world to a theatre of the absurd, hence becoming wolf to fellow man. This is evident in the many atrocities people commit daily, ranging from acts of terrorism, kidnapping, wars, etc. to other minor crimes against humanity.. In view of these, people often question the functionality of conscience of the perpetrators. Others affirm the efficacy of conscience with such comments as ‘my conscience would not allow me commit such evil’, or ‘my conscience is tormenting me’. All this resonate the issues what conscience is, how binding it is, its formation and how to follow the dictates of conscience. This study highlights the importance of understanding conscience as an ethical category and argues that the concept of conscience is a valuable tool for constructing moral systems, overcoming moral dilemmas, and making moral choices. The work adopted qualitative method in collecting and analyzing non-numerical data on the concept of conscience. It maintains that appropriate formation of conscience is necessary for proper judgement, and for the correction of the error in conscience and draws the attention of socializing agents to their roles in conscience formation as the individual conscience is just a microcosm of the conscience of the society.